Evaluating The Potential of Savent Eco-Friendly Coaster as a Catalyst for Sustainability Awareness in Hospitality Education - Kusin, Norfazirah; Aziz, Muhammad Abdul Haq; Japri, Nurul Aidila Suraya (Tropical Scientific Journal, 2026)
Objective: Sustainability in hospitality education is vital for developing environmentally conscious professionals but often faces a gap between theory and practice. This study explores how a tangible eco-innovation of the SAVENT Eco-Friendly Coaster, made from fibrous plant-based (coconut residue) and pulp-based recycled materials which can bridge this awareness-action divide. The coaster was designed as both a sustainable product and a learning tool to promote sustainability awareness among hospitality stakeholders. Using a qualitative exploratory design, data were collected from 125 participants comprising students (68.8%), lecturers (17.6%), and practitioners (13.6%) from Malaysia (76.8%) and Brunei (23.2%). Participants were recruited through institutional emails, social media, and professional networks linked to the SAVENT website. Thematic analysis revealed four key themes: (1) translating sustainability from concept to consciousness, showing strong conceptual understanding; (2) interpreting innovation through a sustainable lens, highlighting recognition of eco-creativity; (3) envisioning applied learning and practice, noting challenges in implementation such as cost and logistics; and (4) cultural and emotional dimension, emphasizing personal and cultural resonance with local materials. The SAVENT coaster demonstrates how experiential, artifact-based learning can transform abstract sustainability principles into practical, emotionally engaging experiences. Overall, the study affirms that tangible eco-innovations can effectively cultivate environmental consciousness in hospitality education. To evaluate how hospitality stakeholders perceive, interpret, and emotionally respond to this tangible, eco-designed artifact, positioning it as a catalyst for sustainability awareness. Research Method: This qualitative exploratory study involved one hundred and twenty-five (N = 125) purposively sampled hospitality stakeholders (students, lecturers, practitioners) from Malaysia and Brunei. Data were gathered via an open-ended Jotform after a website review of the SAVENT project and subsequently analyzed using Braun and Clarke's (2021) thematic analysis. Findings: Findings revealed four interconnected themes: (1) translating sustainability from concept to consciousness; (2) interpreting innovation through a sustainable lens; (3) envisioning applied learning and practical barriers; and (4) cultural and emotional resonance tied to local materials. The results demonstrate that culturally grounded, tangible eco-innovations can serve as symbolic educational artifacts that bridge cognitive and emotional learning, promoting deeper sustainability awareness beyond conventional instruction. Originality: This study provides original insight into a product-based educational approach, demonstrating that culturally grounded eco-innovation using local waste fosters strong personal and emotional engagement, showing that connecting sustainability to local identity significantly enhances awareness beyond theoretical learning